GENETIC OF Panulirus versicolor LOBSTER IN CENDRAWASIH BAY PAPUA AND LOMBOK WATERS WEST NUSA TENGGARA - Bayu Pranata; Abdul Toha Hamid Toha; Duaiht Kolibongso (JURNAL ENGGANO)
The purpose of this study was to determine the level of diversity and genetic relationship of Panulirus versicolor lobsters in Cenderawasih Bay and Lombok waters based on the cytochrome oxidase I (COI) gene. The results showed the level of genetic diversity of the two populations was very high and generally did not differ greatly between populations. We identified 6 haplotypes for P. versicolor lobster populations from Cenderawasih Bay and 7 haplotypes for P. versicolor lobster populations from Lombok waters. Network analysis shows that several P. versicolor lobster individuals from the Cendeawasih Bay and Lombok waters had similar haplotypes. The population of Cenderawasih Bay with Lombok waters was closely related to the average genetic distance value P-distance 0.005 (s.d 0.001) and the results of phylogenetic tree reconstruction showed that the two populations of P. versicolor lobsters form a monophyletic clade (close relatives).